2021
DOI: 10.1111/ijd.15860
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence, and predictors of inflammatory arthritis in patients with hidradenitis suppurativa: a systematic review and meta‐analysis

Abstract: An increasing amount of evidence has emerged suggesting that hidradenitis suppurativa (HS) is associated with inflammatory arthritis. This study reviewed the incidence, prevalence, and predictors of inflammatory arthritis in patients with HS. A comprehensive literature search was conducted in CINAHL, Embase, and Medline from inception to February 14, 2020. Articles were included in the review if they provided data on disease epidemiology or predictors of adult or pediatric HS patients with comorbid inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Given these conditions, the issue of HS comorbidities had long been discussed and was acknowledged as intricate, encompassing several different functional problems including allergic status ( 25 ), gastrointestinal dysfunctions ( 26 , 27 ), and renal diseases ( 28 ). Among the comorbidities of HS, integrated pieces of evidence had suggested that spondyloarthritis and rheumatoid arthritis were of high prevalence and incidence in the HS population ( 6 , 29 ). A recent small-scale case-control study stated that some of the bone function indicators, such as trabecular bone score and hip bone mineral density, were low in patients with HS compared with that in controls ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given these conditions, the issue of HS comorbidities had long been discussed and was acknowledged as intricate, encompassing several different functional problems including allergic status ( 25 ), gastrointestinal dysfunctions ( 26 , 27 ), and renal diseases ( 28 ). Among the comorbidities of HS, integrated pieces of evidence had suggested that spondyloarthritis and rheumatoid arthritis were of high prevalence and incidence in the HS population ( 6 , 29 ). A recent small-scale case-control study stated that some of the bone function indicators, such as trabecular bone score and hip bone mineral density, were low in patients with HS compared with that in controls ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the delay of diagnosis of nearly 2 years after symptom onset, in conjunction with the misdiagnosis with infection, this is likely an underestimate of the true prevalence [24]. HS has an immense physical and psychosocial burden, as it has been associated with increased rates of comorbid depression, anxiety, atopy, and metabolic disorders, as well as inflammatory conditions including inflammatory bowel disease and inflammatory arthritis [23 ▪ ,24,25 ▪ ,26–28]. A newly published systematic review and meta-analysis of 12 studies showed significantly increased odds of asthma and atopic dermatitis among HS patients [26].…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis are more common in HS patients. 21,37 -39 A 2021 meta-analysis found that the total prevalence of inflammatory arthritis is about 1.9% in the HS patient population (95% CI 0.58-6.12). 37…”
Section: Comorbidities Associated With Hsmentioning
confidence: 99%
“…21,37 -39 A 2021 meta-analysis found that the total prevalence of inflammatory arthritis is about 1.9% in the HS patient population (95% CI 0.58-6.12). 37…”
Section: Comorbidities Associated With Hsmentioning
confidence: 99%